IMPACTS OF CLIMATE CHANGE IN THE UPPER BASIN OF THE PIURA RIVER. CANCHAQUE CASE - VELÁSQUEZ-HIDALGO, Oswaldo (2024)
The impacts of the El Niño and La Niña phenomena are analyzed in the context of Climate Change in the upper basin of the Piura River, on the infrastructure and equipment for education, health, basic services, roads and residential, in the district of Canchaque, which was one of the most affected in that region. The type of research is applied, the level is explanatory and the approach is mixed, triangulating qualitative and quantitative methods. The results show that the intense rains associated with El Niño and the prolonged droughts of La Niña considerably affect all services and equipment, in turn aggravating the problems of water scarcity, affecting both agricultural production and the water resources available for human and livestock consumption. Finally, it is concluded that the upper basin of the Piura River, as a whole and Canchaque in particular, present risks and dangers; the measures have been reparativerather than preventive, all social actors face great challenges to mitigate the effects of climate change and adapt to them.